2019
DOI: 10.3390/cells8070647
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Intracellular let-7e, miR-146a, and miR-155 Correlates with Severity of Depression in Patients with Major Depressive Disorder and Is Ameliorated after Antidepressant Treatment

Abstract: Chronic inflammation and abnormalities in Toll-like receptor (TLR) signaling pathways are associated with major depressive disorder (MDD). Our previous work reported that impaired negative regulators for the TLR pathways are associated with MDD. This study aimed to assess the association between the severity of depression and the intracellular microRNAs that regulate TLR4 signaling in both peripheral blood mononuclear cells (PBMCs) and monocytes from MDD patients. The severity of MDD before and after antidepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 54 publications
4
39
1
Order By: Relevance
“…Studies on major depression have found the downregulation of miR-146a in the blood of patients who respond to antidepressant treatment [106]. However, the reverse pattern of miR-146a expression was recently observed in a study using monocytes of depressed patients on antidepressants [107]. With regard to miR-155, knockout mice exhibited reduced depression-like behaviors [67].…”
Section: Cbd and Mirnasmentioning
confidence: 99%
“…Studies on major depression have found the downregulation of miR-146a in the blood of patients who respond to antidepressant treatment [106]. However, the reverse pattern of miR-146a expression was recently observed in a study using monocytes of depressed patients on antidepressants [107]. With regard to miR-155, knockout mice exhibited reduced depression-like behaviors [67].…”
Section: Cbd and Mirnasmentioning
confidence: 99%
“…As noted above, accelerated ageing may be driven by increased ACC [ 81 ], thereby suppressing acetyl-CoA availability for N-ASph, SPMs, and melatonin production. This may be associated with an increase in miR-155, which is evident in stress/depression [ 111 ] and contributes to driving alterations in levels and patterning of immune activity that parallels those in ageing.…”
Section: Integrating Racial Discrimination Into Sars-cov-2 Pathophmentioning
confidence: 99%
“…Notably, a recent study examined miRNA changes in patients that had been prescribed SSRIs, serotonin-norepinephrine reuptake inhibitors and atypical antidepressants and it was shown that miRNA let-7e, miR-146a and miR-155 were low in PBMCs from patients with MDD and, subsequently, increased in response to antidepressant treatment. Two of these miRNA, let-7e and miR-155, were significantly altered following treatment in treatment responders, but not in non-responders [53]. Thus, miRNA may be useful as biomarkers to screen patients for general antidepressant response.…”
Section: Non-coding Rna As Biomarkers Of Drug Responsementioning
confidence: 99%